2008
DOI: 10.3386/w14237
|View full text |Cite
|
Sign up to set email alerts
|

How Does Charitable Giving Respond to Incentives and Income? Dynamic Panel Estimates Accounting for Predictable Changes in Taxation

Abstract: Bill Randolph, and seminar participants at a variety of institutions for valuable discussions on earlier incarnations of the project. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research or the U.S. Department of Treasury. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
2
19
1
1
Order By: Relevance
“…Using a longer but similar panel to that used by Randolph but a different estimation technique, Auten, Sieg and Clotfelter (2002), arrive at the significantly higher estimate of -1.26. More recently, Bakija and Heim (2008) find a long-run value of -.7 -close to Randolph's estimate. Field experiments studying the responses to variations in the match rate offered on donations to individual causes have also found that donations respond to whether or not there is a match but not the size of the match (Karlan and List, 2007;Huck and Rasul, 2009).…”
Section: Introductionsupporting
confidence: 69%
“…Using a longer but similar panel to that used by Randolph but a different estimation technique, Auten, Sieg and Clotfelter (2002), arrive at the significantly higher estimate of -1.26. More recently, Bakija and Heim (2008) find a long-run value of -.7 -close to Randolph's estimate. Field experiments studying the responses to variations in the match rate offered on donations to individual causes have also found that donations respond to whether or not there is a match but not the size of the match (Karlan and List, 2007;Huck and Rasul, 2009).…”
Section: Introductionsupporting
confidence: 69%
“…Using a longer but similar panel to that used by Randolph but a different estimation technique, Auten, Sieg and Clotfelter (2002), arrive at the significantly higher estimate of -1.26. More recently, Bakija and Heim (2008) find a long-run value of -.7 -close to Randolph's estimate. Field experiments studying the responses to variations in the match rate offered on donations to individual causes have also found that donations respond to whether or not there is a match but not the size of the match (Karlan and List, 2007;Huck and Rasul, 2009).…”
Section: Introductionsupporting
confidence: 69%
“…9 If the price elasticity of gross donations is less than unity in absolute value -as suggested by recent estimates (e.g. Randolph, 1995, andBajika andHeim, 2008) -then the effect 7 The figure for total donations is an estimate. However, it suggests that a large proportion of all donations do not attract tax relief.…”
Section: Notes To Tablementioning
confidence: 98%
“…Peloza and Steel (2005) found that when they remove estimates that are more than three standard deviations from the mean, the weighted average of estimates of the elasticity of giving with respect to the tax price is -1.11, within Clotfelter's range. More recently, using a large panel data set that takes advantage of state-level taxes to help in identifying the effects of changes in federal taxes, and accounting for expectations regarding whether tax changes are temporary or permanent, Bakija and Heim (2008) find a tax-price elasticity of giving, with respect to permanent changes in the tax-price, of -0.7, and a lower elasticity for temporary changes to taxes, consistent with the permanent income hypothesis. Brooks (2007) reminds us that only if the tax-price elasticity of donations is greater than one does the increase in donations generated by the tax deduction exceed the foregone tax revenues; if we were indifferent regarding the ''who decides'' question in arts funding, then if the elasticity of giving is less than one the government can get more money to arts organizations by simply granting them the funds directly rather than indirectly through the tax deductibility of donations.…”
Section: Tax Incentives and Tax Reformmentioning
confidence: 54%